2021
DOI: 10.1080/13696998.2021.1928515
|View full text |Cite
|
Sign up to set email alerts
|

Cost-efficiency and expanded access modeling of conversion to biosimilar trastuzumab-dkst with or without pertuzumab in metastatic breast cancer

Abstract: Declaration of financial/other interestsAM has been a speaker and consultant for Pfizer, Coherus, and Viatris. KM and IA are equity shareholders of Matrix45, LLC and, by company policy, are prohibited from owning equity in client organizations (except through mutual funds or other independently administered collective investment instruments) or contracting independently with client organizations. Matrix45 provides similar services to those described in this article to other biopharmaceutical companies on a non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…62 Studies have shown that savings improve when biosimilars are used in place of reference biologics during the treatment of cancer malignancies, resulting in savings to the Medicare program and decreased out-of-pocket cost for patients. 18,63,64 Physicians, hospitals, and other health care clinicians have developed accountable care organizations to offer Medicare patients coordinated care and earn reimbursements on the basis of certain quality metrics-such as decreased costs and the implementation of biosimilars-and improve value for their patient members, in the form of greater savings from lower out-of-pocket costs. 65,66…”
Section: Interchangeabilitymentioning
confidence: 99%
“…62 Studies have shown that savings improve when biosimilars are used in place of reference biologics during the treatment of cancer malignancies, resulting in savings to the Medicare program and decreased out-of-pocket cost for patients. 18,63,64 Physicians, hospitals, and other health care clinicians have developed accountable care organizations to offer Medicare patients coordinated care and earn reimbursements on the basis of certain quality metrics-such as decreased costs and the implementation of biosimilars-and improve value for their patient members, in the form of greater savings from lower out-of-pocket costs. 65,66…”
Section: Interchangeabilitymentioning
confidence: 99%
“…51 Researchers evaluated potential benefits of adding a biosimilar on a budget-neutral basis, allowing expanded access to other treatments. 52 -55…”
Section: Key Elements To Consider In Evaluating Biosimilarsmentioning
confidence: 99%
“…51 Researchers evaluated potential benefits of adding a biosimilar on a budget-neutral basis, allowing expanded access to other treatments. [52][53][54][55] PEs should be conducted initially and regularly throughout the life cycle of the biosimilar given the uncertainty of long-term safety data and the market competition by the reference product or other biosimilars. 47 For example, the introduction of a biosimilar filgrastim in the US market provided a PE framework model to highlight factors impacting the cost-saving of a biosimilar, including the patient, and provider's perceptions.…”
Section: Pharmacoeconomic Evaluationmentioning
confidence: 99%